Urban Environments and the Animal Nuisance: Domestic Livestock Regulation in Nineteenth-Century Canadian Cities - Kheraj, Sean (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2015)
In the nineteenth century, municipal authorities in Canadian cities faced a common set of environmental challenges associated with domestic livestock animals. This article examines the regulation of livestock in Montreal, Toronto, and Winnipeg. As these cities each grew over the course of the nineteenth century, their urban environments became ecologically more alike and their responses to animal nuisances reflected these ecological similarities. Municipal authorities in each of these cities adopted broadly similar approaches to the regulation of livestock animals. Over the course of the nineteenth century, municipal governments developed extensive and increasingly restrictive bylaws, pound systems, and public health regulations to control the use of livestock. These approaches to livestock regulation were the results of emerging common ecological transformations in cities as humans attempted to live together with domestic animals in increasingly densely populated spaces.